تحقيق المراد بمعية الله من خلَل الآثار المروية - Syed Mohammad Chaedar Syed Abdurrahman Al Yahya; Mualimin Mochammad Sahid; Alwi Alatas (Fakulti Pengajian Quran dan Sunnah, 2024)
8TH International Prophetic Conference SWAN 2022 5th to 6th October 2022 (Hybrid Conference) Organized by: Faculty Of Quranic And Sunnah Studies